Case Report: A case study and literature review on teeth discoloration caused by linezolid with the shortest incubation period in a pediatric patient - Le-le, Sun; Qun, Zhao; Lei, Qi; Xiangwei, Meng; Jigang, Si (Frontiers in Pediatrics, 2024)
Background: When it comes to the adverse reactions of linezolid, people always call to mind primarily nausea, vomiting, bone marrow suppression, and so on. Few people are aware of the rare adverse reaction of teeth discoloration.We describe the case of a child affected by bacterial meningitis. After admission, a combination of ceftriaxone and linezolid was administered for anti-infection, and dexamethasone was used to inhibit inflammatory reactions. On the 5th day of treatment with linezolid, the child's teeth appeared brownish color and could not be removed with normal oral hygiene. Upon reviewing the drug instructions and literature, it was found that the discoloration of teeth is a rare adverse reaction of linezolid, which is pseudo discoloration. After stopping the medication for 28 days or up to 5 months, the normal color can be restored. There is no significant impact on the life of the patient, therefore, continue to use linezolid to complete the anti-infection course.Results: After 14 days of anti-infection treatment, the inflammatory indicators of the child decreased to normal, and the condition was close to recovery before discharge.After stopping the medication for 28 days, the color of the teeth returned to normal.Conclusions: This rare adverse reaction sheds light on a previously unreported side effect of this widely used antibiotic. In our case, the discoloration of the teeth occurred earlier, updating the latent period of the adverse reaction.